Development Of Body Temperature Measurement And Face Mask Recognition System - Siti Hawa,; Omar, Rosli (Evolution in Electrical and Electronic Engineering, 2022)
The main purpose of this project is to develop a system that can measure human body temperature and can detect whether a person wearing a face mask or not from a certain distance. This project aims to reduce the rate of infection of this coronavirus 2019 (COVID-19) from spreading among workers. The system developed will be in a single package consisting of Raspberry Pi, infrared thermometer sensor, Raspberry Pi Camera V2 and an ultrasonic sensor to perform the above-mentioned functions. Through experiments, the project manages to achieve its objective successfully as it can perform the temperature measurement either normal which is between 36  to 37.5 , otherwise the door will lock if the high-temperature measurement is more than 37.5  and face mask detection is captured in 10 seconds to display in screen with the accurate name of the employees. The outcomes of this project will make employers easier to monitor their employees’ health status rapidly and contactless to avoiding COVID-19 from spreading.